A profit cap is not yet a general moral duty for companies: a corporate social contract perspective - Kaptein, Muel (Journal of business ethics, 2025)
In both the literature and practice, it has been advocated that companies should have a profit cap. Utilizing corporate social contract theory, this article posits that under at least three conditions, companies do not have a general moral duty to cap their profits. These conditions entail that a company adheres to the contracting principles of its stakeholder relationships, that the constitutive stakeholders of the company have not otherwise stipulated in the corporate social contract, and that the macrosocial contract does not prescribe otherwise to the company. The first two conditions are company-specific and hence do not constitute a generic moral imperative, and there is currently insufficient evidence for the third, generic condition.